HL-A antigens and disease: Acute lymphocytic leukemia - Rogentine, G. Nicholas, Jr.; Yankee, R. A.; Gart, J. J.; Nam, J.; Trapani, R. J. (The Journal of Clinical Investigation, 1972)
50 Caucasian children with acute lymphocytic leukemia (ALL) and 219 members of their families have been genotyped for 15 antigens of the HL-A system. The antigen and gene frequencies for HL-A2 were significantly higher in the patient population than in a 200 member normal Caucasian panel. No other antigen frequencies were significantly elevated. All antigens typed for were found in the patients. No antigen gain or loss was detected in the leukemic cells.